Pembentukan Karakter Kejujuran dan Budaya Manajerial dalam Dokumen Akademik pada Pendidikan Tinggi Vokasi Administrasi Niaga Melalui Pengajaran Bahasa Inggris - Matitaputty, Marcha Stephanie Inapratama; Sari , Hindri Febri Ana (Politeknik Negeri Ambon, 2024)
This study examines the representation of honesty as a core character value in English academic documents within the Department of Business Administration at Politeknik Negeri Ambon. Using a qualitative content analysis approach, the research analyzed syllabi, lesson plans (RPS), textbooks, and assessment materials from four English-related courses. The findings reveal that honesty is most prominently represented in lesson plans and assessment documents through indicators such as anti-plagiarism, transparency, originality, academic integrity, and accountability. Meanwhile, syllabi and textbooks tend to be more general or normative in character integration. Furthermore, the study explores how these educational documents not only reflect ethical principles for students but also embody the managerial culture of the institution, emphasizing transparency, consistency, and institutional accountability. These findings highlight the need for vocational institutions to embed ethical character values into academic practices and managerial governance. Keywords: honesty, character education, vocational education, academic documents, managerial culture